2017
DOI: 10.5194/acp-17-14393-2017
|View full text |Cite
|
Sign up to set email alerts
|

WRF-Chem simulated surface ozone over south Asia during the pre-monsoon: effects of emission inventories and chemical mechanisms

Abstract: Abstract. We evaluate numerical simulations of surface ozone mixing ratios over the south Asian region during the pre-monsoon season, employing three different emission inventories in the Weather Research and Forecasting model with Chemistry (WRF-Chem) with the second-generation Regional Acid Deposition Model (RADM2) chemical mechanism: the Emissions Database for Global Atmospheric Research -Hemispheric Transport of Air Pollution (EDGAR-HTAP), the Intercontinental Chemical Transport Experiment phase B (INTEX-B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 93 publications
6
48
0
Order By: Relevance
“…Although there is no perfect source apportionment technique for nonlinear systems, a reasonable method that tracks mass contributions and accounts for chemical nonlinearity can provide additional information in terms of the design of control strategies (Yarwood et al, 2007). In the tagging method, the photochemical indicator HCHO / NO y with a threshold of 0.28 (Sillman, 1995) was used to determine NO x -or VOC-limited conditions, which can also result in uncertainties in the results. Several other indicators have been proposed to indicate photochemical sensitivity, including O 3 / NO x and O 3 / NO y .…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no perfect source apportionment technique for nonlinear systems, a reasonable method that tracks mass contributions and accounts for chemical nonlinearity can provide additional information in terms of the design of control strategies (Yarwood et al, 2007). In the tagging method, the photochemical indicator HCHO / NO y with a threshold of 0.28 (Sillman, 1995) was used to determine NO x -or VOC-limited conditions, which can also result in uncertainties in the results. Several other indicators have been proposed to indicate photochemical sensitivity, including O 3 / NO x and O 3 / NO y .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Both O 3 and its precursors from different source regions are tracked as independent variables. The ratio of formaldehyde to reactive nitrogen oxides (HCHO / NO y ) was used as proposed by Sillman (1995) to decide whether the grid cell is under NO x or VOC-limited conditions, and then different equations for these two conditions were selected to calculate total O 3 chemical production. A detailed description of the technique is provided in Gao et al (2017a).…”
Section: Ozone Tagging Methods and Setting Of Source Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al () also pointed out that substantial uncertainties exist in the estimated emissions, especially for regions experiencing rapid changes in the economy such as China and India. For instance, a comparison of different anthropogenic emission inventories using WRF‐Chem over Southeast and South Asia has been performed in Amnuaylojaroen et al () and Sharma et al (). Amnuaylojaroen et al () showed that the uncertainties of carbon monoxide surface mixing ratios in simulations with different anthropogenic emission inventories reach 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Amnuaylojaroen et al () showed that the uncertainties of carbon monoxide surface mixing ratios in simulations with different anthropogenic emission inventories reach 30%. Sharma et al () showed that the modeled ozone mixing ratios during noontime are sensitive to the choice of an emission inventory.…”
Section: Introductionmentioning
confidence: 99%